Kontribusi Mahasiswa dalam Mendukung Kemajuan Indonesia - Islamiyah, Nur (Maliki Interdisciplinary Journal, 2025)
Students, as the younger generation with higher education, play a crucial role in advancing Indonesia, especially in addressing challenges in education, economics, and politics. This article discusses the role of students as agents of change and their contributions to building a better Indonesia. Students contribute by improving the quality of education, promoting technological innovation, developing entrepreneurship, raising environmental awareness, and strengthening national values and integrity. Through these roles, students can significantly contribute to achieving the Vision of Golden Indonesia 2045, which envisions the country as a developed nation with a strong economy, prosperous society, and integrity-driven governance. This article also emphasizes the importance of instilling morality, ethics, and social values in the change movements led by students. With active involvement and idealistic spirit, students are expected to become the cornerstone of building a better and more sustainable nation.